2021
DOI: 10.1177/1359105321999088
|View full text |Cite
|
Sign up to set email alerts
|

Finding the silver lining in the COVID-19 crisis

Abstract: Research has confirmed there is a silver lining to many aversive experiences and that negative occurrences can be an opportunity for post-traumatic growth (PTG). To investigate benefit-finding in the COVID-19 crisis, 179 MTurk workers were surveyed. Participants reported dips in satisfaction with work, leisure, fitness, mental health, and finances in the midst of the pandemic, relative to 6 months prior and in the future. Benefit-finding in COVID-19 was significantly related to PTG, coping, gratitude, and ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
7
26
0
Order By: Relevance
“…This study provides evidential insight for planning public messaging and mental health interventions in future lockdowns and restrictions. While some research has reported negative emotions and risks to mental health [8,9], our findings of silver linings to the early stages of the pandemic aligns with other work demonstrating human tendencies to adapt and notice positives [23,24]. Despite the turmoil resulting from the pandemic's global spread with its challenging personal impacts across health, social and economic domains, many of the Australians in this study found silver linings in their experiences and hoped that some changes would endure even after COVID-19 was controlled.…”
Section: Discussionsupporting
confidence: 88%
“…This study provides evidential insight for planning public messaging and mental health interventions in future lockdowns and restrictions. While some research has reported negative emotions and risks to mental health [8,9], our findings of silver linings to the early stages of the pandemic aligns with other work demonstrating human tendencies to adapt and notice positives [23,24]. Despite the turmoil resulting from the pandemic's global spread with its challenging personal impacts across health, social and economic domains, many of the Australians in this study found silver linings in their experiences and hoped that some changes would endure even after COVID-19 was controlled.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, lower age and female gender, along with lower resilience and less adaptive defensive functioning, were predictors of stress [ 38 , 50 , 66 ]. Even in non-healthcare workers, coping strategies were common methods for dealing with the new conditions dictated by the pandemic [ 34 ]. In teachers, similarly to healthcare workers, avoidance coping strategies were associated with higher stress and reduced positive psychological outcomes [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar inconsistent findings regarding PPTG and psychological adjustment have been reported in the pandemic. Positive associations of PPTG and distress have been reported in a community sample in Spain (PTSS; Vazquez et al, 2021 ), a sample of nurses in Taiwan (burnout; Chen et al, 2021 ), a sample of dental personnel in Canada, France and Israel (depression and worry; Uziel et al, 2021 ), a sample of community residents in Greece (perceived stress; Koliouli and Canellopoulos, 2021 ), a national sample of US veterans (PTSD symptoms; Pietrzak et al, 2021 ), a snowball sample of people in Turkey (PTSS and perceived depreciation; Ikizer et al, 2021 ), and an online sample in the US (mental health; Kowalski et al, 2021 ). In China, a study of nurses and the general population found PPTG was unrelated to anxiety ( Li et al, 2021 ) and another of high school graduates found PPTG unrelated to anxiety or depression ( Yu et al, 2021 ).…”
Section: Relations Of Pptg With Better Psychological Adjustmentmentioning
confidence: 99%